Assessing the Perception of Media and Communication Researchers in UNILAG on Web Analytics as an Audience Research Method (Journal of Advanced Research in Social Sciences, 2023)
Web analytics, which reference the collection and analysis of information via internet sites, are being increasingly adopted by media organizations in carrying out research on audiences. It is unclear if this same trend is visible in academia despite the adoption of online tools to carry out research. Web analytics provide a view of audience behavior online and may prove relevant in excavating data about audiences and their preferences in media and communication research. It is, however, important to understand the perception of media and communication researchers to this audience research method. The study utilized the survey method to investigate four research hypotheses on the adoption of web analytics, perceptions on the relevance of data derived from web analytics and perception of reliability and trustworthiness of web analytics as an audience research method. The results indicate that media and communication researchers in UNILAG were significantly familiar with web analytics, and perceived it as a trustworthy source for data gathering.